Distal shoe with stainless steel crown for space maintainer in primary teeth: clinical case - Quintana del Solar, Carmen (2009)
When the deciduous second molar is lost before first permanent molar eruption, intraalveolar space maintainer, it is indicated as an alternative to solve this problem caused by partial or total loss of primary tooth. This appliance allow the reestablishment of its functions appropriately. This paper shows a case report for distal shoe space maintainer with stainless steel crown in a children of 5 years and 2 months.